Use of transposase and ends of IS608 enables precise and scarless genome modification for modulating gene expression and metabolic engineering applications in Escherichia coli. Issue 1 (18th September 2015) - Thakker, Chandresh; Lin, Kevin; Martini‐Stoica, Heidi; Bennett, George N.
Abstract: Various methods have been developed for gene disruption in bacteria; however, extra in vitro manipulation steps or the residual presence of a scar in the host chromosome limits the use of such methods. By utilizing the unique properties of ISHp608, we have developed a simple and precise method for genome manipulation in Escherichia coli that alters the gene sequence without leaving foreign DNA in the chromosome. This strategy involves PCR amplification of a DNA cassette containing ISHp608‐LE (left end)‐antibiotic resistance gene‐counterselection marker‐ISHp608‐RE (right end) by using primers containing extensions homologous to the adjacent regions of the target gene on the chromosome. The λ Red mediated recombination of the PCR product and antibiotic resistance screening results in transformants with a modified gene target. The ISHp608‐LE‐antibiotic resistance gene‐counterselection marker‐ISHp608‐RE cassette can then be excised using a temperature sensitive plasmid expressing the TnpA transposase, which precisely cleaves ISHp608‐LE and ISHp608‐RE without leaving a scar sequence. We demonstrated lacZ gene point mutation repair, two precise disruptions of the lacZ gene and constructed a library of lacZ variants having variable β‐galactosidase activity by changing its ribosome binding site sequences using the ISHp608 system. This technique can be used in E. coli genome modification and could be extended for use in other bacteria. Abstract : A new method for precise modification of a desired sequence in a bacterial genome is presented. The method relies on: (i) recombination for introducing a DNA module that bears the desired change in its chromosome; and (ii) precise excision of the carrier portion of the module to generate the final desired change. This is done without additional DNA sequences being left behind.